Avaliação transversal da qualidade de vida em crianças e adolescentes com paralisia cerebral por meio de um instrumento genérico (CHQ-PF50) - Morales, Nívea de Macedo Oliveira (2005)
The objectives of the study were to evaluate the psychometric properties of Child Health Questionnaire (CHQ-PF50), Brazilian version, in children and adolescents with cerebral palsy (CP) and the health-related quality of life (HRQL) in this group against those of healthy people, considering the clinical types, severity of motor involvement and presence of epilepsy. The parents or guardians of children and adolescents 5 to 18 years old, with CP classified as spastic, extrapyramidal or ataxic, seen at AACD-MG, were asked to answer the CHQ-PF50 by self-administered technique, between December 2003 and April 2004. The scores were compared with those of healthy people and according to clinical types, severity of motor involvement and presence of epilepsy. The motor function was evaluated through the Gross Motor Function Measure. The motor severity was classified as mild, moderate and severe according to Gross Motor Function Classification System. The following psychometric properties were studied: missing data, floor effect, ceiling effect, item internal consistency, internal consistency reliability, item discriminant validity, discriminant validity, convergent validity, divergent validity, criterion validity, concurrent validity and construct validity. Ninety six parents or guardians answered the questionnaire. The patients age ranged from 5 to 17.9 years old (mean: 9.3). Psychometric properties were considered adequate. Patients scored significantly lower than healthy population in almost all scales, except on change on health, with large effect size in the summary of physical scores (4.4) and psychosocial scores (1.8). Summary of physical scores were significantly lower in quadriplegic patients, in severe form or in presence of epilepsy. There were no significant differences in the summary of psychosocial scores according to clinical types, severity level and presence of epilepsy. The results showed that CHQ-PF50 Brazilian version have adequate psychometric properties to be applied in patients with CP. By caregivers perception, CP had an important negative impact on HRQL in children and adolescents including physical, emotional and social well-being of patient and their families. The repercussion on physical construct is greater in quadriplegic patients, with severe form of CP or with epilepsy.